Road sediment production and delivery: effects of fires, traffic, and road decommissioning - Sosa Peréz, Gabriel, author; MacDonald, Lee H., advisor; Kampf, Stephanie, committee member; Lefsky, Michael, committee member; Butters, Gregory, committee member (Colorado State University. Libraries, 2016)
Unpaved roads often are a major source of sediment to streams in forested watersheds, and an increase in sediment production and delivery can adversely degrade water quality and aquatic habitat. The first part of this study quantifies the effects of wildfires on road erosion and road-stream connectivity as a function of fire severity and road segment characteristics. The data were collected along 6.8 km of an unpaved road after the High Park wildfire in Colorado. The second and third parts of this dissertation investigate how traffic and two road decommissioning treatments affect road sediment production and road-stream connectivity through the use of rainfall simulations, sediment production measurements at the road segment scale, and repeated surveys of 12.3 km of decommissioned roads. The segment-scale and road survey data were collected over a three-year period that included one summer prior to decommissioning and the first two years after decommissioning. The road-wildfire study indicated that road surface rill erosion increased with hillslope burn severity due to the increasing amounts of runoff, but the length and area of rilling also increased with road segment slope. Segments with a slope ≤5% tended to capture sediment from the hillslope. Road segment area was only important for roads in areas burned at low severity, indicating that hillslopes become a progressively less important source of runoff as burn severity decreases. All of the road segments in areas burned at moderate and high severity and 78% of the segments in areas burned at low severity were connected to the stream due to the increased runoff from upslope, the concentration of hillslope and road surface runoff to a single drainage point, and the reduced infiltration and trapping capacity of the hillslopes below the road. After wildfires land managers need to increase the frequency of drainage structures, and a more integrated modeling approach is needed to further our understanding of the complex interactions between burned hillslope and roads. The rainfall simulations showed that the infiltration capacity for the decommissioning treatment of only ripping had little effect on infiltration and significantly increased sediment yields compared to closed roads. Mulching after ripping doubled the final infiltration rate and decreased sediment yields by nearly a factor of five compared to only ripping. Eighty passes of an all-terrain vehicle on two closed roads had no effect on infiltration capacity, but increased sediment yields by a factor of three. The results at the road segment-scale showed that traffic was the dominant control on sediment production, and both decommissioning treatments greatly reduced road sediment production as nearly all of the eroded sediment was trapped in the furrows. Decommissioning reduced road-stream connectivity from 12% of the total length to only 2%, with most of the connected segments being immediately adjacent to a stream. These results can help calibrate and validate road erosion models, and guide the design of future road decommissioning treatments.